Confinement Effects in Catalysis Using Well-Defined Materials and Cages - Mouarrawis, Valentinos; Plessius, Raoul; van der Vlugt, Jarl Ivar; Reek, Joost N. H. (Frontiers in Chemistry, 2018)
This review focuses on the effects of confinement on the selectivity and activity of molecular and heterogeneous catalysts with well-defined structure. A general introduction is provided about catalysis and how the working principles of enzymes can be used as a source of inspiration for the preparation of catalysts with enhanced performance. Subsequently, relevant studies demonstrate the importance of second coordination sphere effects in a broad sense (in homogeneous and heterogeneous catalysis). First we show some illustrative examples of heterogeneous catalysts where confinement influences catalytic performance. These examples include materials that form well-defined structures such as zeolites, MOFs and COFs. Second, specific cases of homogeneous catalysts where non-covalent interactions determine the selectivity and activity are treated in detail. This includes examples based on cyclodextrins, calix[n]arenes, cucurbit[n]urils and self-assembled container molecules. Throughout the review, the impact of confined spaces is emphasized and put into context, in order to get a better understanding of the effects of confinement on catalyst performance. In addition, this analysis intends to showcase the similarities between homogeneous and heterogeneous catalysts, which may impose the development of novel strategies in the realm of catalysis.